“Pateada”: - Luiz Paulo Pimentel de Souza (Revista Brasileira de Estudos da Presença)
Historically, the theater spectator has been constituted as a central figure in both theatrical practice and theory, becoming the target of an artistic-pedagogical discourse. Starting from this premise, this article aims to problematize the game play between conduct and counter-conduct in which the theater spectator was entangled. To do so, we propose to observe an extinct practice in Brazilian theaters but prevalent throughout the 19th century – the “pateada” – which involved a noisy stomping of feet by the audience with the purpose of interrupting a performance. Resorting to the analysis of the “pateada”, we present a historical moment in which the behavior and subjectivity of the spectator would begin to be regulated towards a disciplined, moderated, and pedagogized body, and a new type of public-stage address would emerge.